Preparation of Nimodipine Loaded Microspheres: Evaluation of Parameters: Preparation of nimodipine loaded microspheres - Atyabi, Fatemah; Mohammadi, Afsaneh; Dinarvand, Rassoul (Iranian Journal of Pharmaceutical Sciences, 2005)
The purpose of this study was to prepare and characterize nimodipine loaded microspheres using ethyl cellulose (EC) as a carrier polymer through an emulsion solvent evaporation method. These evaluations characterized the pattern of drug release from prepared microspheres. Nimodipin loaded microspheres were prepared using an emulsification solvent evaporation method. The effect of process variables such as stirring rate, drug polymer ratio in the organic phase, the viscosity of the dispersed phase and the emulsifier concentration, on the morphology of microspheres, particle size distribution, drug content and in vitro release profile of nimodipine were investigated. The prepared microspheres were spherical with smooth surface. The mean diameter of microspheres decreased with increasing the concentration of the emulsifier in the continuous phase and stirring rate of the medium. However, increasing the viscosity of the dispersed organic phase increased the particle size of microspheres. Both the drug and polymer concentration in the organic phase increased the entrapment of nimodipine in ethyl cellulose microspheres. Drug content of the microspheres was lowered by increasing the viscosity of the dispersed phase and increasing the concentration of poly vinyl alcohol. The rate of drug release from microspheres was directly influenced by the drug to polymer ratio, as any increase in this ratio allowed the higher release rates from microspheres. The higher the polymer concentration the lower was the rate of drug release from microspheres.